Electromagnetic Emission of Rocks after Large-Scale Blasts; Journal of Mining Science; Vol. 54, iss. 2 - Bespalko (Bespal'ko) A. A. Anatoly Alekseevich; Yavorovich L. V. Ludmila Vasilievna; Eremenko A. A. Andrey Andreevich; Shtirts V. A. Vladimir Aleksandrovich (2018, 2018)
Title screen